2001
DOI: 10.1046/j.1526-0976.2001.51012-9.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Preventive Care by Prompting Physicians

Abstract: Arch Intern Med 2000;160:301–8 This meta‐analysis of randomized trials of physician prompts to improve screening rates found that prompts do improve the rate of performing various health maintenance interventions. A prompt is defined as anything that tells a clinician to perform a screen. The most common prompts are stickers posted to charts of patients coming in for care and computer notices generated at the time of scheduled appointment. The effects on Pap smear screening rates were significantly less than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 0 publications
0
62
0
1
Order By: Relevance
“…We used a modified Delphi method 26 to reach consensus on which variables to extract from study reports. We first compiled a list of factors studied in previous systematic reviews of computerised clinical decision support systems [20][21][22][23][24] and independently rated the importance of each factor on a 10 point scale in an anonymous web based survey. We then reviewed survey results and agreed on operational definitions for factors that we judged important and feasible to extract from published reports.…”
Section: Selecting Factors For Analysismentioning
confidence: 99%
“…We used a modified Delphi method 26 to reach consensus on which variables to extract from study reports. We first compiled a list of factors studied in previous systematic reviews of computerised clinical decision support systems [20][21][22][23][24] and independently rated the importance of each factor on a 10 point scale in an anonymous web based survey. We then reviewed survey results and agreed on operational definitions for factors that we judged important and feasible to extract from published reports.…”
Section: Selecting Factors For Analysismentioning
confidence: 99%
“…Examples include manual or computer based systems that attach care reminders to the charts of patients needing specific preventive care services and computerised physician order entry systems that provide patient-specific recommendations as part of the order entry process. Such systems have been shown to improve prescribing practices,57 reduce serious medication errors,8 9 enhance the delivery of preventive care services,10 11 and improve adherence to recommended care standards 4 12. Compared with other approaches to improve practice, these systems have also generally been shown to be more effective and more likely to result in lasting improvements in clinical practice 13 – 22…”
Section: Introductionmentioning
confidence: 99%
“…The advent of the electronic medical record (EMR) offers opportunities to provide patient-specific reminders and decision support to improve screening rates, often combining EMR functions with medical practice system changes 10 11 12 13 14 15 16 17 18. Increasingly, investigators are recognising that primary care practice improvement requires changes in physician and staff roles as part of effective teams, with medical assistants (MAs) serving a key role 19…”
Section: Strategies To Improve Screeningmentioning
confidence: 99%
“…Implementation of EMR-based reminders or prompts has been shown to improve CRC screening rates, although provider compliance with prompts is variable 11 12 13 14 15 17. For example, an early (1996) study found that more than half of electronic reminders did not lead to recommended testing 14.…”
Section: Strategies To Improve Screeningmentioning
confidence: 99%